Identidade e metamorfose de uma transfada em busca por reconhecimento em um contexto social de caça às bruxas - Rodrigues, Fernanda Bravo (2022)
The present work has as its field of questioning the identity and the struggle for recognition of a trans woman in front of social institutions. Thus, the general objective of this research is to analyze the metamorphoses in the process by subjective recognition from the life story narrative of our participant. As specific objectives, we seek to: a) discuss with the participant how ways of recognition are constructed/negotiated in her life trajectory; b) perceive how she metamorphoses her subjectivities in front of the social discourse that (de)recognizes her as feminine; c) understand how the process of resistance to cisheteronorm by a trans woman, produces or not a collective recognition. In order to achieve the objectives, this research was based on five theoretical and/or methodological contributions: Identity studies from the perspective of Critical Social Psychology, post-structuralist feminist studies, the stigma theory, the Recognition and Transfeminism theory, which absorbs the perspectives of decolonial feminism and intersectional black feminism. This study has a qualitative approach, whose collection method uses life story narratives as a materiality of identity, as well as an analytical object for the intended studies. Hence, the dissertation is composed of four sections: 1) Introduction; 2) Human identity as metamorphosis and the reverberations of these studies on Trans Identities; 3) History and “Stories” - Trans women: from the Inquisition to social movements; 4) In a political context of witch-hunting: a resistant counter-narrative of a transfairy who defines herself as Luana. Due to the Covid-19 pandemic, the invitation to the participant was made via digital social network (WhatsApp), as well as her interview took place through the Google Meet platform. We intend to analyze how our narrator negotiates her identity subjectivities in her life trajectory, from the cisheteronormative discursive limits. This study contributes to critical discussions about identity and transfeminist studies and to fostering public policies to reduce oppressions naturalized to female trans identities. From the narrative of our collaborator, we perceive metamorphoses in the course of her struggle for recognition as well as social processes in becoming that are metamorphosing in the face of social intolerance to everything that escapes cisheteronormative standards.